2021
DOI: 10.3389/fimmu.2021.614773
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Transcriptomic Analysis Reveals the Role of the Immune Checkpoint HLA-G Molecule in Cancers

Abstract: Human leukocyte antigen G (HLA-G) is known as a novel immune checkpoint molecule in cancer; thus, HLA-G and its receptors might be targets for immune checkpoint blockade in cancer immunotherapy. The aim of this study was to systematically identify the roles of checkpoint HLA-G molecules across various types of cancer. ONCOMINE, GEPIA, CCLE, TRRUST, HAP, PrognoScan, Kaplan-Meier Plotter, cBioPortal, LinkedOmics, STRING, GeneMANIA, DAVID, TIMER, and CIBERSORT were utilized. Gene Ontology (GO) and Kyoto Encyclope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…HLA-G can interact with the inhibitory receptor Immunoglobulin-Like Transcript 2 (ILT2) in the blood and be secreted as a free soluble form (sHLA-G) or through extracellular vesicles [ 47 ]. Recently, new approaches revealed that the blockage of the HLA-G/ILT axis, could be insightful for the development of effective anti-tumor treatments strategies [ 59 , 60 , 61 ]. Since HLA-G exists in several polymorphs that affect both the protein expression levels and its peptide-binding cleft, targeting peptide binding cleft of the most common HLA-G polymorphs can also be suggested as a therapeutic strategy [ 31 ].…”
Section: Functions Of Hla-g In Diseasesmentioning
confidence: 99%
“…HLA-G can interact with the inhibitory receptor Immunoglobulin-Like Transcript 2 (ILT2) in the blood and be secreted as a free soluble form (sHLA-G) or through extracellular vesicles [ 47 ]. Recently, new approaches revealed that the blockage of the HLA-G/ILT axis, could be insightful for the development of effective anti-tumor treatments strategies [ 59 , 60 , 61 ]. Since HLA-G exists in several polymorphs that affect both the protein expression levels and its peptide-binding cleft, targeting peptide binding cleft of the most common HLA-G polymorphs can also be suggested as a therapeutic strategy [ 31 ].…”
Section: Functions Of Hla-g In Diseasesmentioning
confidence: 99%
“…Although these new immunotherapies represent a huge improvement in the field of cancer therapies, early or late resistance emerge in the majority of the patients [ 1 , 2 ]. There is thus a high medical need to better understand the mechanisms underlying the control of immune checkpoint gene expression that is so far essentially described at the transcription level [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…NF‐κB can promote tumour survival via modifying apoptosis, cause inflammatory microenvironment by interacting with interleukins, and affect NSCLC survival [ 34 ]. Meanwhile, HLA‐G , a member of the MHC class I, is a well‐established immune checkpoint that plays an important regulatory role in tumour immune response [ 35 , 36 ]. HLA‐G can inhibit the functions of NK and T cells, suppress the immune response, help tumour cells escape immune surveillance, and lead to poor prognosis of NSCLC patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%